Peluang Badan Aspirasi Masyarakat DPR RI Untuk Memperkuat Demokrasi Partisipatoris [The Role of BAM in Enhancing Indonesia's Participatory Democracy] - Prayudi, Prayudi (Jurnal Politica, 2025)
Badan Aspirasi Masyarakat (BAM), a complementary organ of the Indonesian House of Representatives, has generated new expectations for the establishment of participatory democracy in Indonesia, a more meaningful democracy beyond merely procedural or administrative formalities. However, amidst the presence of a large governing coalition and the persistent sectoral egos following the 2024 general elections, the realization of participatory democracy remains challenging. For the Indonesian House of Representatives, the efforts of the complementary organs in managing public complaints and aspirations should continue to be pursued, while also positioning BAM as a frontline institution for fostering participatory Democracy. The early period of the 2024–2029 legislative term indicates that BAM has taken constructive steps in responding to the public aspirations while also undergoing a process of internal consolidation, both in terms of its membership and organizational support systems. Despite the ongoing restructuring of the Indonesian House of Representatives, including the increase of the number of complementary organs from 11 to 13, BAM continues to have positive prospects for contributing to the broader consolidation of political representation in the future. This paper analyzes the opportunities for BAM as a complementary organ of the Indonesian House of Representatives to strengthen the realization of participatory democracy at the national level. It is recommended to reformulate the duties and authorities of the complementary organs, particularly with regard to the establishment of BAM, both in UU MD3 and in the Indonesian House of Representatives' Rules of Procedure.AbstrakBadan Aspirasi Masyarakat (BAM) sebagai alat kelengkapan dewan (AKD) DPR RI telah melahirkan harapan bagi terciptanya demokrasi partisipatoris di Indonesia yang lebih tertata secara politik dan bukan sekedar prosedural administratif. Masalahnya, di tengah koalisi pemerintahan yang besar dan masih kuatnya ego sektoral setelah Pemilu 2024, maka perwujudan bagi demokrasi partisipatoris bukan hal mudah diwujudkan. Bagi DPR RI, relasi antar AKD dalam menangani pengaduan dan aspirasi masyarakat menjadi faktor yang masih harus diperjuangkan dalam menempatkan BAM agar menjadi garda terdepan bagi perwujudan demokrasi partisipatoris. Perkembangan DPR RI hasil Pemilu 2024 yang masih tergolong di awal periode keanggotaannya di tahun 2025 ini cenderung menunjukkan beberapa langkah BAM dalam menangani aspirasi masyarakat yang masuk dan proses konsolidasi internal keanggotaan dan organisasi sistem pendukungnya terlihat cukup kondusif. Meskipun dalam penataan kembali infrastruktur politik pelaksanaan fungsi-fungsi kelembagaan, termasuk penambahan jumlah Komisi sebagai AKD dari 11 menjadi 13, secara umum BAM tetap memiliki prospek yang positif bagi upaya konsolidasi perwakilan politik rakyat dimasa mendatang. Tulisan ini menganalisis peluang BAM sebagai alat kelengkapan dewan dalam memperkuat perwujudan demokrasi partisipatoris di ranah nasional. Direkomendasikan agar dilakukan reformulasi tugas dan kewenangan AKD DPR RI utamanya atas munculnya BAM baik di tingkat UU MD 3 maupun peraturan tata tertib DPR RI.